Effectiveness of a multicomponent intervention to promote physical activity during the school day: rationale and methods of the MOVESCHOOL study - Bandera-Campos, Francisco J.; Grao-Cruces, Alberto; Camiletti-Moirón, Daniel; Martín-Acosta, Fátima; Muñoz-González, Raúl; González-Pérez, María; Ruiz-Hermosa, Abel; Vaquero-Solís, Miguel; Padilla-Moledo, Carmen; Sánchez-Oliva, David (Frontiers in Public Health, 2025)
BackgroundIncreasing levels of physical activity (PA) and reducing sedentary time among adolescents during the school day is a pressing need. Emerging methodologies and strategies been shown to be effective in increasing PA levels and providing additional benefits for students, such us physically active lessons (PAL), active breaks (AB) and active recesses (AR). However, evidence concerning adolescents remains limited. This manuscript presents the methods and rationale of the MOVESCHOOL study, which aims was to examine the effects of a multicomponent school-based intervention during the school day on indicators of PA, sedentary time, health, executive functions and education in adolescents.MethodsA quasi-experimental study was conducted with the aim to involve a total of 800 students aged 12–14 years old from 11 schools (7th and 8th grade) in south-western Spain, five schools forming the intervention group and six schools forming the control group. The evaluation included two independent measurements: pre-intervention and post-intervention. The intervention lasted 29 weeks and consisted of a multi-component programme including a weekly PAL, two 5 min daily AB, and a daily AR. Primary outcomes included accelerometer-based PA and sedentary time, health-related physical fitness, academic indicators, and executive functions. For statistical analyses, descriptive, correlational, regression, and repeated measures ANOVA analyses will be applied. Additionally, qualitative data were gathered through semi-structured individual interviews and focus groups, and information will be evaluated with thematic analysis.DiscussionThe MOVESCHOOL study represents a pioneering effort in Spain, being the first of its kind to evaluate the effectiveness of a multicomponent programme in secondary schools. Furthermore, this project provides valuable insights into the effects of a multicomponent school-based PA intervention on PA levels, sedentary time, health-related, cognitive, academic indicators and psychological health markers in secondary school students. The results of this study will make a significant contribution to the educational community, providing them with innovative teaching methods and strategies that have the potential to increase PA levels during the school day. In addition, this research promises to provide a transformative experience for educators, equipping them with tools to promote the holistic development of their students, enriching their academic performance and enhancing their well-being.Clinical trial registrationClinicalTrials.gov, identifier NCT06254638.